Physical and mechanical properties of coconut palm (Cocos nucifera) stem (Bangladesh Journal of Scientific and Industrial Research, 2015)
A study was conducted on coconut palm (Cocos nucifera) stem of Khulna region in Bangladesh. Important physical and mechanical properties were studied for 40-year-old tree. The test was done at different height positions (i.e., top, middle and bottom) and lateral positions (i.e., core and periphery). The average air dry and oven dry density of coconut stem was 400 and 460 kg/m3, respectively. The MOE and MOR values for air dry and oven dry conditions were 2374 and 2633 N/mm2 and 27.30 and 30.44 N/mm2. The compression strength in parallel to grain and perpendicular to grain for air dry and oven dry conditions were 12.41 and 12.85 N/mm2 and 9.28 and 9.64 N/mm2, respectively. There is a possibility to use the stem of coconut palm for different structural purposes.Bangladesh J. Sci. Ind. Res. 50(1), 39-46, 2015